Droplet impacts onto soft solids entrap more air - Langley, KR; Castrejon Pita, A; Thoroddsen, ST (Royal Society of Chemistry, 2020)
We investigate the effects of surface stiffness on the air cushioning at the bottom of a liquid drop impacting onto a soft solid and the resulting entrapment of a central bubble. This was achieved using ultra-high-speed interferometry at 5 million frames per second and spatial resolution of 1.05 μm per pixel. The soft solid delays the effects of gas compressibility resulting in much larger air discs than corresponding impacts onto rigid surfaces. Using an effective impact velocity equal to half of the actual impact velocity brings the soft solid scaling behavior better in line with rigid substrate scaling. We also observe extended gliding of the drop as it initially avoids contact with the surface spreading over a thin layer of air and investigate the threshold velocity for the transition from gliding to ring contact. Such extended gliding layers have previously been seen for high-viscosity drop impacts, but not for low-viscosity liquids at the impact velocities used herein.